1992
DOI: 10.1113/jphysiol.1992.sp019113
|View full text |Cite
|
Sign up to set email alerts
|

The location of the receptors involved in the human diuretic response to drinking an isotonic electrolyte solution.

Abstract: 1. This study aimed to shed light on the receptors involved in the diuretic response to drinking isotonic fluids in man by employing a polyethylene glycol-based bowel lavage solution (Golytely) which is reported to cause no net movement of fluid across the gut. 2. Drinking Golytely resulted in a transient hypotonic diuresis. Mean urine flow rose from control values of 0.9 ml min-1 to 10.1 ml min-1 70 min after the start of drinking. The increase in urine output was accompanied by a fall in urine osmolality fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this respect the recent demonstration that atrial natriuretic peptide, like anti-diuretic hormone (ADH) and aldosterone, exerts its effects on the intestine, as well as the kidney (Matsushita, Nishida, Hosomi & Tanaka, 1991), may be important. Similarly, Crotty, Gebruers & Hall (1992) have suggested that the diuretic response to isotonic electrolyte drinking may be partly mediated by enteric receptors and by hormones other than ADH. Vasoactive intestinal peptide could well be involved since it has natriuretic effects and both its plasma concentration and its metabolic clearance rate are affected by sodium intake (Davis, Shelley, MacDonald & Duggan, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect the recent demonstration that atrial natriuretic peptide, like anti-diuretic hormone (ADH) and aldosterone, exerts its effects on the intestine, as well as the kidney (Matsushita, Nishida, Hosomi & Tanaka, 1991), may be important. Similarly, Crotty, Gebruers & Hall (1992) have suggested that the diuretic response to isotonic electrolyte drinking may be partly mediated by enteric receptors and by hormones other than ADH. Vasoactive intestinal peptide could well be involved since it has natriuretic effects and both its plasma concentration and its metabolic clearance rate are affected by sodium intake (Davis, Shelley, MacDonald & Duggan, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These findings show no physiological basis on which to support this practice. Infusion of a bowel-lavage solution into the stomach of man leads to a hypotonic diuresis (Crotty et al 1988). Unlike physiological saline, bowellavage solutions, based on sodium sulphate and polyethylene glycol, are associated with minimal absorption or secretion (Davis et al 1980).…”
mentioning
confidence: 99%